2021
DOI: 10.1136/bmjopen-2020-047004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of virtual and augmented reality for improving knowledge and skills in medical students: protocol for a systematic review

Abstract: IntroductionVirtual reality (VR) and augmented reality (AR) technologies are increasingly being used in undergraduate medical education. We aim to evaluate the effectiveness of VR and AR technologies for improving knowledge and skills in medical students.Methods and analysisUsing Best Evidence in Medical Education (BEME) collaboration guidelines, we will search MEDLINE (via PubMed), Education Resources Information Center, PsycINFO, Web of Knowledge, Embase and the Cochrane Central Register of Controlled Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…However, other studies have found that the correlation between online games and aggressive behaviors is not significant [ 23 , 24 ]. In addition, practical games are widely used in multiple areas of education, healthcare, sustainability projects, training, and consultancy, but their effectiveness varies due to differences in the designs [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, other studies have found that the correlation between online games and aggressive behaviors is not significant [ 23 , 24 ]. In addition, practical games are widely used in multiple areas of education, healthcare, sustainability projects, training, and consultancy, but their effectiveness varies due to differences in the designs [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…AR and VR usage among students and residents has been shown to be successful in facilitating learning and understanding neuroanatomy. 11,18,19 However, a clean and precise dissection of cadaveric brain specimens and displaying critical neuroanatomic structures from a surgical perspective are imperative for more sophisticated surgical neuroanatomy education. Therefore, meticulous dissections by neurosurgeons are generally preferred and considered the gold standard method for studying and teaching microsurgical neuroanatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a systematic review protocol was found by McNamara et al in the Prospero system that questioned how immersive technology has been used to teach clinical skills in medical education. And how have these abilities been assessed and their effectiveness quanti ed (12)? Another systematic review reported in 2021 by Bartit et al found that the use of these immersive, salient, motivating, and engaging technologies was effective in most cases, but few studies reported that no difference in effectiveness had been seen (13).…”
Section: Systematic Review Registrationmentioning
confidence: 99%